Knowledge and entrepreneurship propensity in Central European countries: An analysis in universities - Jaroslav Belas; Dalia Streimikiene; Jan Dvorsky; Martina Jakubcinova; Andrea Bencsik (Journal of Innovation & Knowledge)
The motives for starting a business among university students represent a current and important topic of scientific research. A key scientific premise of this approach is that significant research has demonstrated the importance of entrepreneurial activities by university-educated entrepreneurs in contributing to economic and social development worldwide. This study aims to identify the key factors that determine the propensity of university students to engage in entrepreneurship in selected Central European countries and to present a comprehensive model. The empirical research, focused on investigating university students’ attitudes towards entrepreneurial opportunities, was conducted in the V4 countries (Slovakia, Hungary, Poland, and the Czech Republic) between March and June 2024. The research included 2310 respondents, defined as students currently studying at higher education institutions providing economic-social, university, or college education. Data collection was conducted using Google Forms. Structural equation modelling (SEM) was used to evaluate the statistical hypotheses. The strongest influence on university students’ propensity to engage in entrepreneurship was demonstrated by government support for entrepreneurship. The second most significant factor was the quality of the macroeconomic environment, followed by access to external financing. The final statistically significant factor in the model was the effect of education. Surprisingly, factors such as the quality of the entrepreneurial environment and the perceived advantages and disadvantages of entrepreneurship did not show a statistically significant effect on shaping students’ entrepreneurial inclination. The results of this study are relevant not only for the academic community but also for policymakers and education management, as they reveal considerable gaps in the field. These findings provide clear signals to national government officials that entrepreneurship education receives insufficient attention at universities in the selected Central European countries. Furthermore, a broader societal debate on the importance of entrepreneurship among university-educated individuals should be encouraged, as they are better positioned to ensure sustainable company growth through continuous innovation and the application of sophisticated business management approaches.